The stage of adolescence transition: analysing the competitiveness and employability of Generation Z in Indonesia - Adhi Cahya Fahadayna; Agung Sugeng Widodo; Isma Adila; Adam Hendra Brata; Mikchaell Alfanov Pardamean Panjaitan (International Journal of Adolescence and Youth)
Globalization has significantly led to increased human mobility and intensified competition in the job market. With its large population surplus and a predominantly productive generation, Indonesia also faced this challenge. The article aims to identify strategies for preparing and providing Generation Z with the skills and portfolios demanded by the evolving job market. This research employs two main methods. The first method uses a quantitative paradigm with a questionnaire to measure Generation Z’s self-assessment of their competitiveness derived from the dynamic capabilities framework by Finch et al. The second method implements a qualitative paradigm, employing focus group discussion to provide an in-depth analysis of the identified phenomenon of employability. This research successfully unpacked the integrated dynamic competitiveness of Generation Z, including intellectual, job-specific, personality, and meta-skills resources. These findings are crucial for each university to consider the Generation Z conditions during the work transition.